Cognitive disorders in people who have had COVID-19 - Dzeruzhinskaya Наталія; Statetska Еліна (Psychosomatic Medicine and General Practice, 2025)
Relevance. COVID-19 infection has a significant damaging effect on the cognitive functions of people who have had this infection, and also causes changes in their emotional state. The study of the causes and features of clinical manifestations of cognitive and emotional disorders in such individuals is necessary to develop effective diagnostic methods and develop a rehabilitation program to improve their social functioning. The aim of the study was to develop a rehabilitation program for people with cognitive and emotional disorders due to COVID-19 infection by analyzing the severity and structure of their cognitive impairment and studying the associated emotional symptoms. Materials and Methods. The study was based on the results of a survey of people of different ages who had cognitive and emotional disorders due to COVID-19. The study was conducted using theoretical (literature review) and empirical methods (psychodiagnostic methods - Montreal Cognitive Assessment (MoCA), Schulte Tables, 10 Words by A. R. Luria, Hospital Anxiety and Depression Scale (HADS)). Results and Discussion The severity and structure of cognitive and emotional disorders differ by age. Older people have more severe cognitive impairment and a higher proportion of anxiety disorders, while younger people have less cognitive deficits and a prevalence of depressive symptoms. The most common disorders in both age groups are memory and sensorimotor reaction time disorders. Conclusions. Rehabilitation programs for these individuals should be aimed at reducing cognitive deficits, concomitant emotional disorders, and improving their social functioning. Programs should be personalized, taking into account the specifics of the disorders in each case.